Reconstruction of the Islamic Cooperative Business Model in the Era of Disruption: Integration of Digital Platforms and the Green Economy Based on Maqasid Shariah - Pristiyanto Pristiyanto (Universitas KH. Abdul Chalim Mojokerto, 2026)
The era of digital disruption has transformed the global economic landscape, including the Islamic cooperative (Koperasi Syariah) sector in Indonesia. This transformation demands a business model reconstruction that is not only responsive to technology but also aligned with sustainability principles and Shariah values. This study employs a Systematic Literature Review (SLR) methodology, analyzing 30 top publications from 157 screened articles. Findings reveal that reconstruction requires three main pillars: Maqasid Shariah foundation, digital platform integration, and green economy practices. The proposed five-component framework provides a holistic roadmap for sustainable and Shariah-compliant cooperative transformation.